A pathological, bacteriological and serological approach to leg problems in broilers - Deniz Mısırlıoğlu; K; Tayfun Çarlı; Aiper Sevimli; Metin Petek (Eurasian Journal of Veterinary Sciences)
Leg problems in 4 flocks having 4443. 6154, 6070 and 6200 birds, respectively in a commercial broiler farm wore investigated in this study, A total o( 72 lame chickens was selected randomly of the 3th week of age and examined pathologically, bacteriologically and serologically. At the end of production, the total mortality rates in Ihe flocks were calculated as 10,46%, 10.33%, 9.83%, 10.61%, respectively. The rates ol leg problem- related deaths in the total deaths of the flocks were 15.48%, 14.77%, 16,75%, 12.15%, respectively. Escherichia coli (27.94%), Staphylococcus aureus (7.35%), Salmonella enteritidis (1.47%) and Enlerobacter spp (1.47%) were isolated from the affected joints. Anti-Reovirus and Mycoplasma gallisepticum antibodies were not detected. Pathological examination showed evidence ot purulent tenosynovitis, femoral head lesions, osteomyelitis and septicemia.